2019
DOI: 10.1098/rsta.2018.0128
|View full text |Cite
|
Sign up to set email alerts
|

Complex partial synchronization patterns in networks of delay-coupled neurons

Abstract: We study the spatio-temporal dynamics of a multiplex network of delay-coupled FitzHugh–Nagumo oscillators with non-local and fractal connectivities. Apart from chimera states, a new regime of coexistence of slow and fast oscillations is found. An analytical explanation for the emergence of such coexisting partial synchronization patterns is given. Furthermore, we propose a control scheme for the number of fast and slow neurons in each layer. This article is part of the theme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 102 publications
0
24
0
Order By: Relevance
“…Recently, a prominent line of research emerged which studies chimera states in multilayer networks [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Multilayer networks are important modelling tools for complex systems such as transportation networks, social interactions and the brain [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a prominent line of research emerged which studies chimera states in multilayer networks [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Multilayer networks are important modelling tools for complex systems such as transportation networks, social interactions and the brain [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…Nikitin et al [15] study partially synchronized solutions in coupled FitzHugh-Nagumo oscillators. The authors found a new regime of coexisting slow and fast oscillations in a twolayer network with identical units, which coexist with chimera states.…”
Section: Content Of the Issuementioning
confidence: 99%
“…Examples also include air transportation networks, power grids, coupled semiconductor lasers, communication networks, social networks, infectious disease, etc. [1][2][3][4][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%